Yeast Estrogen Screen Assay as a Tool for Detecting Estrogenic Activity in Water Bodies - Mirjana Bistan; Mojca Podgorelec; Romana Marinšek Logar; Tatjana Tišler (Food Technology and Biotechnology, 2012)
The presence of endocrine-disrupting compounds in wastewater, surface water, groundwater and even drinking water has become a major concern worldwide, since they negatively affect wildlife and humans. Therefore, these substances should be effectively removed from effluents before they are discharged into surface water to prevent pollution of groundwater, which can be a source of drinking water. Furthermore, an efficient control of endocrine-disrupting compounds in wastewater based on biological and analytical techniques is required. In this study, a yeast estrogen screen (YES) bioassay has been introduced and optimized with the aim to assess potential estrogenic activity of waters. First, assay duration, concentration of added substrate to the assay medium and wavelength used to measure the absorbance of the substrate were estimated. Several compounds, such as 17-β-estradiol, 17-α-ethinylestradiol, bisphenol A, nonylphenol, genisteine, hydrocortisone, dieldrin, atrazine, methoxychlor, testosterone and progesterone were used to verify its specificity and sensitivity. The optimized YES assay was sensitive and responded specifically to the selected estrogenic and nonestrogenic compounds in aqueous samples. Potential estrogenicity of influent and effluent samples of two wastewater treatment plants was assessed after the samples had been concentrated by solid-phase extraction (SPE) procedure using Oasis® HLB cartridges and methanol as eluting solvent. Up to 90 % of relative estrogenic activity was detected in concentrated samples of influents to wastewater treatment plants and estrogenic activity was still present in the concentrated effluent samples. We found that the introduced YES assay is a suitable screening tool for monitoring the potential estrogenicity of effluents that are discharged into surface water.